The relationship between nasopharyngeal CCL5 and microbiota on disease severity among infants with bronchiolitis - Hasegawa, Kohei (Allergy, 2017)
Emerging evidence suggests that the airway microbiota plays an important role in viral bronchiolitis pathobiology. However, little is known about the combined role of airway microbiota and CCL5 in infants with bronchiolitis. In this multicenter prospective cohort study of 1,005 infants (age <1 year) hospitalized for bronchiolitis during 2011–2014, we observed statistically-significant interactions between nasopharyngeal airway CCL5 levels and microbiota profiles with regard to the risk of both intensive care use (P(interaction)=0.02) and hospital length-of-stay ≥3 days (P(interaction)=0.03). Among infants with lower CCL5 levels, the Haemophilus-dominant microbiota profile was associated with a higher risk of intensive care use (OR, 3.20; 95%CI, 1.18–8.68; P=0.02) and hospital length-of-stay ≥3 days (OR, 4.14; 95%CI, 2.08–8.24; P<0.001) compared to the Moraxella-dominant profile. Conversely, among those with higher CCL5 levels, there were no significant associations between the microbiota profiles and these severity outcomes (all P≥0.10).